Perbandingan Nilai Kerusakan Jalan Menggunakan Metode Pavement Condition Index (PCI) dengan Surface Distress Index (SDI) pada Ruas Jalan Irigasi, Kecamatan Gambut, Kabupaten Banjar - Riska Hawinuti (Jurnal Teknologi Berkelanjutan, 2026)
Road maintenance is a crucial aspect for sustaining smooth transportation flow and fostering economic growth. Over time, pavement deterioration is inevitable, necessitating an objective and quantifiable condition assessment. Irigasi Road, serving as the research location, is a primary artery in Malintang Baru Village and plays a vital role by connecting various public facilities, including the village head office, schools, community health centers, and the local market. It also provides access to residential complexes and functions as an alternative connecting route between two national roads: the Banjarmasin-Banjarbaru route via Ahmad Yani Street and the Banjarmasin-Banjarbaru route via Liang Anggang Street, through Trisakti Port. Several common distresses were observed on the flexible pavement of this road, likely attributable to underlying soft soil conditions, frequent passage of heavy loaded vehicles, and the annual inundation of some road sections during the floods in early 2025. The objective of this study is to assess the pavement distress condition of Irigasi Road using the Pavement Condition Index (PCI) and the Surface Distress Index (SDI) methods, and subsequently to determine the appropriate rehabilitation strategy based on the field survey results. The overall calculation results across all segments yielded an aggregate PCI value of 66,51, indicating that the recommended maintenance action is “Routine/ Periodic Maintenance”. Conversely, the calculated SDI value was 31,127, classified as “Good”, which recommends a maintenance program of “Routine Maintenance”.